Un’esperienza di psicoterapia in presenza in tempi di pandemia - Monacelli, Carla (Il sogno della farfalla, 2021)
The aim of this article is to enter into the debate aroused during the pandemic between psychotherapists who decided to carry out online therapeutic session and those who did refrain from it. During the lockdown from March until June 2020, the author and her group’s participants maintained the previously established rapport by using a WhatsApp group chat. In June the in-presence sessions started again, and the topic of “distancing” and “summer break” were the first to be faced. Among the most relevant pillars of Massimo Fagioli’s Theory of Birth which include setting, transfer and interpretation, the first was the undoubtedly the most affected. This was mainly because of the drastic changes determined by the health emergency which led to the definition of new time, duration and reduction in the number of group participants.